(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
In this paper we generalize the idea of balanced and semibalanced maps in type-2 fuzzy sets. The notion of type-2 fuzzy G-equivalence and G-congruence on a groupoid are introduced and some properties related to these notions have been established.